Mesenchymal stem cells: properties and clinical application - A. P. Lykov (Сибирский научный медицинский журнал, 2023)
Mesenchymal stem cells (MSCs) are multipotent stromal cells that can diﬀerentiate into various cell types, including adipocytes, osteocytes, chondrocytes, etc. MSCs can be isolated from various human and animal tissues. MSCs are characterized by high proliferative capacity, diﬀerentiation in the connective-tissue direction, paracrine and trophic activity (they produce a wide range of biologically active molecules), are capable of migrating to the zone of organ and tissue damage, and exhibit immunosuppression. There are similarities and diﬀerences between human and mammalian MSCs in phenotype and functional activity. The therapeutic potential of MSCs has been shown on experimental models and in clinical trials, which allows us to consider the MSC-oriented cell technologies as an alternative to traditional methods of treatment. The article presents a review and analysis of the literature devoted to the study of MSCs properties, signaling pathways involved in the regulation of cell activity, the prospects for the use of MSCs in the treatment of inﬂammatory and degenerative diseases. During preparation of the review full-text, free access articles for the period from 2006 to 2022 were taken from eLibrary and National Center for Biotechnology Information (NCBI) databases.